Study Qualitative Motivate the Nurse in Centralization Management Medicinize at Space Take Care of to Lodge Sedap Malam RSUD Gambiran Kediri Town - heriyanto, Heriyanto; Novita Ana Anggraini; Alfian Fawzi (Journal of Global Research in Public Health, 2016)
Hospital accreditation standards for centralized drug systems are one of the priorities that must be met by hospitals. This system functions to use drugs appropriately and avoid waste in their use, so that patient nursing care needs can be met. The purpose of this study was to explore nurses' motivation in centralizing drug management in the treatment room. The design used is descriptive qualitative, the research sample was taken from nurses on duty in the inpatient room of Sedap Malam RSUD Gambiran Kediri City who were willing to be interviewed, with a sample size of 6 informants. Data collection with a tape recorder through in-depth interviews with 6 nurses (6 informants). The results of the study of achievement factors, increasing the status of the job itself, responsibility, work environment conditions, regulations of the treatment room and hospital, relationships within the group, and subordinate superior relationships that showed the highest influence on implementing centralized drug management in the room were factors of regulations of the treatment room and hospital. All informants had the same overall reason, namely that the implementation of centralized drug management in the room was carried out based on regulations that had been mutually agreed upon so that the implementation of centralized drug management could be arranged in accordance with service procedures in the hospital. Factors that influence nurses at Gambiran Regional Hospital, Kediri City in implementing centralized drug management in the room are factors of treatment room and hospital regulations because the regulations that have been set must be implemented so that the implementation of drug centralization continues to run according to procedures and to meet hospital accreditation standards. The procedures in implementing centralized drug management are not only joint provisions, but also become provisions in accordance with the procedures that have been set by the hospital accreditation commission.